2006
DOI: 10.2807/esw.11.16.02944-en
|View full text |Cite
|
Sign up to set email alerts
|

Imported cases of chikungunya in metropolitan France, April 2005 - February 2006

Abstract: By 9 April 2006, 241 000 cases of chikungunya had been reported on the island of Reunion, and 5339 cases on the island of Mayotte. The islands of Mauritius, Seychelles, Madagascar, and Comoros are also affected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
19
0
3
Order By: Relevance
“…The majority of hospitalized atypical cases occurred in February and March 2006; this time period coincides with the period of the highest reporting of Chikungunya fever cases on Re´union ( Fig. 1) [9,10].…”
Section: Between 1 April 2005 and 31mentioning
confidence: 72%
“…The majority of hospitalized atypical cases occurred in February and March 2006; this time period coincides with the period of the highest reporting of Chikungunya fever cases on Re´union ( Fig. 1) [9,10].…”
Section: Between 1 April 2005 and 31mentioning
confidence: 72%
“…Consequently, in 2005 and2006, especially mainland France (Cordel et al 2006, Krastinova et al 2006), but also other European nations (Depoortere and Coulombier 2006), reported a sudden increase in imported CHIKV infections. The need for CHIKV surveillance in Europe was driven home by the autochthonous outbreak of CHIKV infections in central Italy in 2007 (Rezza et al 2007, Angelini et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…47 Varios trabajadores de laboratorio también contrajeron la infección por CHIKV después de manipular sangre infectada. 48 Estas exposiciones indican que puede ocurrir transmisión por contacto directo.…”
Section: Manejo De Los Casosunclassified
“…Hay casos documentados de infecciones adquiridas por personal de laboratorio que manipulaba sangre infectada y de un trabajador sanitario que extrajo sangre a un paciente infectado. 47,48 Estos casos apoyan la hipótesis de que es posible la transmisión del CHIKV a través de hemoderivados.…”
Section: D Seguridad De La Sangre óRganos Y Tejidosunclassified